2019
DOI: 10.29119/1641-3466.2019.136.48
|View full text |Cite
|
Sign up to set email alerts
|

Quality Culture Research in Higher Education– Literature Review

Abstract: The aim of this article is to identify and discuss research problems, methods and conclusions existing in the studies on quality culture in higher education institutions. A systematic review of literature was used. The study was conducted on the basis of 27 peerreviewed, English-language scientific articles published in academic journals. These papers were selected based on the list of excluding (i.g. type of the publication, etc.) and including criterions (i.g. keywords, etc.). There are three conclusions. Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
1
0
Order By: Relevance
“…A review of previous literature has shown that most studies related to quality culture are qualitative in nature (Adina-Petruţa, 2014; Njiro, 2016; Bendermacher et al. , 2017; Lycke and Tano, 2017; Tutko, 2019). As far as quantitative studies are concerned, quality culture has been mainly investigated as a predictor variable in relation to organizational performance, and the results showed a positive effect on organizational performance (Ali and Musah, 2012; Koskei et al ., 2015; Wu, 2015; Ullah et al ., 2016; Hilman et al ., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A review of previous literature has shown that most studies related to quality culture are qualitative in nature (Adina-Petruţa, 2014; Njiro, 2016; Bendermacher et al. , 2017; Lycke and Tano, 2017; Tutko, 2019). As far as quantitative studies are concerned, quality culture has been mainly investigated as a predictor variable in relation to organizational performance, and the results showed a positive effect on organizational performance (Ali and Musah, 2012; Koskei et al ., 2015; Wu, 2015; Ullah et al ., 2016; Hilman et al ., 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Even though QC is a widely used term, its meaning remains unclear due to a lack of consensus (Nygren-Landgärds et al, 2022). In previous literature, researchers mainly investigated QC in qualitative studies (Adina-Petruţa, 2014;Njiro, 2016;Bendermacher et al, 2017;Lycke and Tano, 2017;Tutko, 2019). While in quantitative studies QC has been mainly investigated as a predictor variable in relation to organizational performance, and the results showed a positive effect on organizational performance (Ali and Musah, 2012;Katwalo and Asienga, 2015;Wu, 2015;Ullah et al, 2016;Hilman et al, 2017).…”
Section: Mediating Effect Of Quality Culturementioning
confidence: 99%